Healthy Eating: Nutritious Snacking Crossword - Emily Minton (EDIS, 2010)
FCS8905, a 1-page illustrated handout by Emily Minton, provides a simple crossword puzzle activity to learn more about smart snacking. Published by the UF Department of Family Youth and Community Sciences, May 2010.